Pengaruh Stresor Kerja dan Persepsi Sanksi Organisasi terhadap Perilaku Cyberloafing di Universitas Jember (The Impact of Work Stressors and Organizational Sanctions Perception on Cyberloafing Behavior in Jember University) - Meilisa Fani Herdiati; Anita Dewi Prahastuti Sujoso; Ragil Ismi Hartanti (Pustaka Kesehatan, 2015)
One of the negative consequencies of internet is cyberloafing behavior. Cyberloafing refers to employee’s behavior of using their work internet access during work hours for non-work-related purposes. Based on the preliminary study, there were more than 50% of University Jember's administrative employee use their working time to cyberloaf. They spent one hour a day in average to cyberloaf. The aims of this research were to examine the impact of work stressors (role ambiguity, role conflict, role overload) and perception of organizational sanction on cyberloafing behavior in Jember University by using analytical survey method. Sample of this research were 80 administrative government’s employee of 14 faculties and 2 study programs in Jember University. The data was analyzed by simple and multiple linier regression. The univariat analysis result indicated that the employee had low role ambiguity, role conflict, and role overload, but high organizational sanctions perception, and they spent one our a day in average to cyberloaf. The bivariat analysis result indicated that role conflict, role overload, and perception of organizational sanction had significant impact on cyberloafing behavior, while role ambiguity did not. Keywords: role ambiguity, role conflict, role overload, organizational sanctions perception, cyberloafing.